Study to assess existing knowledge of headache disorders among registered osteopaths practising in the UK: A cross-sectional survey. (March 2022) - Huzzey-Cunningham, Elizabeth; McWilliam, Mark; Mahtani, Vinod; Bridge, Helena; Breukel, Corina; Schytz, Henrik Winther; Draper-Rodi, Jerry
Abstract: Background: Headache disorders are highly prevalent worldwide. Many headache sufferers search for answers outside medical and pharmaceutical models. Complementary and alternative medicine (CAM) including osteopathy are widely used by headache patients. Indeed 9% of patients consulting osteopaths do so for headaches. There is no existing assessment of headache knowledge among practising Osteopaths in the UK. Methods: This study was a cross-sectional survey employing an anonymous online questionnaire. An original questionnaire was developed. The scope was based on established guidelines in the primary care setting. Multiple choice and closed-ended questions assessed knowledge of the diagnostic criteria, potential red flags and appropriate investigations. The answers were informed by the International Classification Headache Disorder (ICHD-3) and the British Association for the Study of Headaches (BASH) guidelines. Three case vignettes relevant to osteopathic practice were included. Participants were invited to give optional free text feedback. The questionnaire was open to be self-completed by participants for 30 days. Results: There were 398 responders of which 383 were included and all of whom completed the questionnaire. The study found areas where knowledge was good, areas where it was limited and areas of uncertainty. The mean knowledge score was 6.93 out of 10 (range 2.18–9.42). There was a significantly lower mean knowledge score in those who had no prior headache education of −0.716 with a difference in means (−1.075 to −0.353, 95% C.I.) compared to those with prior education. Gender and years qualified had no significant effect on mean knowledge score. Optional free text feedback was given by 81 (21.2%) of the respondents and analyzed. The main themes were acknowledgment of knowledge gaps and a desire for more headache education. Conclusion: The findings suggest there are gaps in the existing knowledge on headache among UK osteopaths and the extent of this is dependent on prior headache education. We propose that ongoing headache education among osteopaths is needed in the field.